BRAND AGRICULTURE AND ECONOMIC GEOGRAPHY: WHEN ARE HIGHLY DIFFERENTIATED PRODUCTS SUSTAINABLE IN THE REMOTE PERIPHERY?. Issue 3 (12th September 2019) - Fujita, Masahisa; Hamaguchi, Nobuaki
Abstract : This paper presents a general equilibrium model of new economic geography, incorporating brand agriculture that produces differentiated agricultural products. Focusing on the core‐periphery space, we show that highly differentiated brand agriculture can be sustained in the periphery even when access to the core market is not particularly good. This result supports the promotion of innovative products in rural areas in order to avoid direct price competition in generic commodities markets under unfavorable conditions.